Content analysis of the 2010 Iraqi Parliamentary election: a comparative study of CNN and al-Jazeera (English) - Hussein, Hataw H. Saleh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This study focuses on the objectivity in the coverage of the 2010 Iraqi parliamentary election by CNN and Al-Jazeera in their websites. The news coverage was examined for 42 days from 12 February until 26 March 2010, from the starting day of the election campaign to the announcement of the election results. The total samples collected were 112 stories, of which 38 of them were from CNN and 74 from AlJazeera. The data were coded for sources of news (official and non-official), direction of the news stories (favourable, unfavourable and balanced/neutral), and frames (responsibility, conflict and human impact frame) to test whether there is any significant variation between the two networks in their coverage of the event. Quantitative Content Analysis as a research method is used to investigate how the networks objectively covered this election. The Chi-square analysis yielded many significant findings which clearly distinguished AI-Jazeera as covering the election more objectively than CNN based on their comprehensive usage of news frames, presence of balanced/neutral news and employment of varied news sources. Even though one hundred percent of objectivity will never be attained as argued by scholars, in this study it can be concluded that AI-Jazeera, in comparison with CNN, displayed more objectivity in its coverage ofthe 20 I 0 Iraqi parliamentary election.